The impact of service quality on multifunctional leisure centres client loyalty: evidence from Lithuania - Jasinskas, Edmundas; Fominienė, Vilija; Simanavičius, Artūras; Ūsas, Antanas; Simkovič, Aleksandra (Transformations In Business & Economics, 2026)
This study examines how service quality influences client loyalty in Lithuanian multifunctional leisure centres. A quantitative survey of 385 participants was conducted using an integrated assessment based on SERVQUAL, SQAS, and QUESC models, along with the LSSS loyalty scale. Results revealed a consistent negative gap between client expectations and actual service experience, indicating that services often fail to meet consumer demands. Despite this gap, all service quality dimensions showed a significant positive relationship with loyalty. Price, equipment quality, and sports programs emerged as the strongest predictors of loyal behaviour. Findings highlight the importance of improving perceived value, modernising equipment, and diversifying programs to strengthen client retention. The findings offer practical implications for multifunctional leisure centre managers seeking to enhance customer retention and loyalty by improving service quality, particularly in pricing, program offerings, and facility equipment.
Keywords: service quality; loyalty; evaluation models